2022
DOI: 10.1126/sciadv.abm7154
|View full text |Cite
|
Sign up to set email alerts
|

Fast equilibration mechanisms in disordered materials mediated by slow liquid dynamics

Abstract: The rate at which a nonequilibrium system decreases its free energy is commonly ascribed to molecular relaxation processes, arising from spontaneous rearrangements at the microscopic scale. While equilibration of liquids usually requires density fluctuations at time scales quickly diverging upon cooling, growing experimental evidence indicates the presence of a different, alternative pathway of weaker temperature dependence. Such equilibration processes exhibit a temperature-invariant activation energy, on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 56 publications
7
53
0
Order By: Relevance
“…Way more beneficial would be trying to understand the overwhelming experimental activity showing the existence of multiple mechanisms of equilibration; how this complex behavior can affect aspects of extraordinary importance such as vitrification, [45] crystal nucleation, [46,47] and ionic conductivity [48] ; and the development of theoretical approaches able to capture this phenomenology. [49][50][51][52] DATA AVAILABILITY STATEMENT The data that support the findings of this study are available from the corresponding author upon reasonable request. ORCID Daniele Cangialosi https://orcid.org/0000-0002-5782-7725 Angel Alegría https://orcid.org/0000-0001-6125-8214 Juan Colmenero https://orcid.org/0000-0002-2440-4953…”
mentioning
confidence: 84%
“…Way more beneficial would be trying to understand the overwhelming experimental activity showing the existence of multiple mechanisms of equilibration; how this complex behavior can affect aspects of extraordinary importance such as vitrification, [45] crystal nucleation, [46,47] and ionic conductivity [48] ; and the development of theoretical approaches able to capture this phenomenology. [49][50][51][52] DATA AVAILABILITY STATEMENT The data that support the findings of this study are available from the corresponding author upon reasonable request. ORCID Daniele Cangialosi https://orcid.org/0000-0002-5782-7725 Angel Alegría https://orcid.org/0000-0001-6125-8214 Juan Colmenero https://orcid.org/0000-0002-2440-4953…”
mentioning
confidence: 84%
“…Recently, Song et al reported slower processes in PS and other polymers above their glass transition temperatures. 34 The authors related the slow process to the time scale for spontaneous rearrangements and equilibration in liquids, while the molecularlevel mechanism is still unclear. This observation is consistent with Lupasçu et al's former work that also observed slow relaxation processes in PS.…”
Section: Macromolecules Pubsacsorg/macromolecules Articlementioning
confidence: 99%
“…It was found that due to H-bonds, most likely some kind of ordering, similar to the nematic one, is present in this system . Finally, it should be mentioned that very recent studies on a series of thin polymer films demonstrated that the presence of the relaxation process, slower than the α-mode, could be a general feature of glassy dynamics and, therefore, does not originate from any kind of polymeric features …”
Section: Resultsmentioning
confidence: 65%
“…To justify this thesis, it should be reminded that in contrast to the α′-mode observed in PMMS, the slow processes assigned to the helical conformations detected in polystyrene (treated with various solvents) show an Arrhenius-like behavior and do not merge with the segmental relaxation . The same pattern of behavior applies to the slow mode detected in the series of thin films, which was supposed to be a universal feature of glass-forming materials . Finally, our last molecular dynamics simulations indicated that although PMMS molecules tend to arrange themselves in a nematic-like order, this process is clearly driven by the H bonds formed by the thiol moiety .…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation